2008
DOI: 10.4269/ajtmh.2008.79.558
|View full text |Cite
|
Sign up to set email alerts
|

Filarial/Human Immunodeficiency Virus Coinfection in Urban Southern India

Abstract: The disease course of human immunodeficiency virus (HIV) is often altered by existing or newly acquired coinfections. Treatment or prevention of these concomitant infections often improves the quality and duration of life of HIV-infected persons. The impact of helminth infections on infections with HIV is less clear. However, HIV is frequently most problematic in areas where helminth infections are common. In advance of the widespread distribution of drugs for elimination of lymphatic filariasis, we assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In a previous study, we have looked at the coinfection prevalence rates in India by surveying serum samples of HIV infected patients for filaria antigens. We found a prevalence of 5–9.5% of filarial antigenemia in HIV+ patients, similar to the prevalences found in the HIV negative population in the same region [ 16 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a previous study, we have looked at the coinfection prevalence rates in India by surveying serum samples of HIV infected patients for filaria antigens. We found a prevalence of 5–9.5% of filarial antigenemia in HIV+ patients, similar to the prevalences found in the HIV negative population in the same region [ 16 ].…”
Section: Introductionsupporting
confidence: 86%
“…We found a much lower than expected rate of W . bancrofti positivity in the HIV population in and around Chennai, although our sample size calculations were based on our 2004 prevalence data in which we found that 9.5% of HIV positive subjects were filarial also antigen positive [ 16 ]. India, like other LF endemic countries of the world, is participating in the Global Program to Eliminate Lymphatic Filariasis (GPELF), and is distributing single dose diethylcarbamazine (DEC) and albendazole on a population-wide level in some endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…But, there is very little data available on the prevalence of lymphatic filariasis (LF) among people with diabetes, although studies have examined the coexistence of LF with HIV [3], malaria [4] and tuberculosis [5]. Current estimates suggest that 129 million persons worldwide are infected with one of the three lymph-dwelling filariae ( Wuchereria bancrofti , Brugia malayi or B. timori ), the major causative agents of LF.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of concomitant infections is of primary importance in the delaying of disease progression in HIV-infected individuals. HIV have been reported to be accompanied with a constellation of various opportunistic infections in the course of the disease (3,6,7) . A study by Nielsen et al reported an overall HIV prevalence of 7.9% and a 43.5% prevalence of W. bancrofti specific circulating filarial antigen (CFA) among 907 adults in the Tanga region of Tanzania (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic filariasis is caused by a thin thread-like parasite that lives in the lymph vessels, causing a significant disability in infected people. The course of HIV depends on several factors such as the host, viral strain, type of treatment and environmental situations are part of the factors that determine the disease progression in an HIVinfected host (3) . Treatments of concomitant infections in HIV-infected persons have been adopted in slowing down the progress of HIV disease and to prolong life expectancy (4,5) .…”
Section: Introductionmentioning
confidence: 99%